CdSe/ZnS Quantum Dot-to-ZnO Nanowires Charge Transfer Dynamics for Enhanced Efficiency Quantum Dot-Sensitized Solar Cells. Issue 1638 (13th February 2014) - Sadeghimakki, Bahareh; Jahed, Navid Mohammad Sadeghi.; Janfeshan, Bita; Dashmiz, Shadi; Sivoththaman, Siva
ABSTRACT: Core-shell quantum dots (QDs) with enhanced photostability compared with bare QDs are promising light absorbers for solar cell applications. In this work, electron injection from excited CdSe/ZnS QDs to Zinc Oxide (ZnO) nanowires (NWs) prepared by two techniques were demonstrated. Arrays of ZnO NWs were fabricated by hydrothermal growth and etching. ZnO NWs were sensitized with hydrophobically ligated colloidal CdSe/ZnS QDs. The electron transfer dynamic in QD/ZnO NW architecture was examined using photoluminescence (PL) and decay lifetime analyses. The quenching of the QD emission peak and lowered average lifetime in QD/ZnO NW architecture confirms the deactivation of the excited QDs via electron transfer to ZnO NWs. Electron transfer was enhanced by using smaller QDs. This study provides insight on charge transfer dynamics at the QD/ZnO NW interface in order to engineer high performance quantum dot sensitized solar cells (QDSSCs).